2018
DOI: 10.1111/jgs.15447
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Nursing Home Entry: A Prognostic Model for Older Adults with a Family or Unpaid Caregiver

Abstract: We developed a prognostic model and simple scoring system that may be used to stratify risk of long-term NH entry of community-living older adults. Our model may be useful for population health and policy applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 45 publications
(94 reference statements)
0
32
5
1
Order By: Relevance
“…However, regarding HC, although difficult to compare, similar rates were observed between homebound incidence in Japan 41 (32.1 per 1000 individuals/year) and that of our study (30.6 per individual/year). With respect to NH entry, we found lower rates than those reported by the USA 42 , 16.1% in two years; but closer to Germany, with rates of 4.7% in a three-year follow-up 43 . Again, institutionalization rates differ among countries, depending on organizational aspects, the availability of long-term beds and the responsibility for the care of disabled older individuals by different actors.…”
Section: Incidence Of Home Care and Nursing Home Entrycontrasting
confidence: 65%
“…However, regarding HC, although difficult to compare, similar rates were observed between homebound incidence in Japan 41 (32.1 per 1000 individuals/year) and that of our study (30.6 per individual/year). With respect to NH entry, we found lower rates than those reported by the USA 42 , 16.1% in two years; but closer to Germany, with rates of 4.7% in a three-year follow-up 43 . Again, institutionalization rates differ among countries, depending on organizational aspects, the availability of long-term beds and the responsibility for the care of disabled older individuals by different actors.…”
Section: Incidence Of Home Care and Nursing Home Entrycontrasting
confidence: 65%
“…However, regarding HC, although di cult to compare, similar rates were observed between homebound incidence in Japan [41] (32.1 per 1000 individuals/year) and that of our study (30.6 per individual/year). With respect to NH entry, we found lower rates than those reported by the USA [42], 16.1% in two years; but closer to Germany, with rates of 4.7% in a three-year follow-up [43].…”
Section: Incidence Of Home Care and Nursing Home Entrycontrasting
confidence: 61%
“…Research indicates that in addition to older adults' demographic characteristics and functional level, risk of nursing home utilization is also affected by factors related to family caregiving circumstances and experiences . One study examined the effect of California's PFL law on nursing home utilization by older adults in the state.…”
Section: Benefits Of Pflmentioning
confidence: 99%
“…5 Research indicates that in addition to older adults' demographic characteristics and functional level, risk of nursing home utilization is also affected by factors related to family caregiving circumstances and experiences. 22 One study examined the effect of California's PFL law on nursing home utilization by older adults in the state. The research found that the use of PFL by employed family caregivers in California showed an 11% reduction in older adults' nursing home utilization in that state between 1999 and 2008.…”
Section: Benefits Of Pflmentioning
confidence: 99%